Politik Hukum Pengakuan Hak Masyarakat Adat dalam Rancangan Undang-Undang Masyarakat Hukum Adat - Krismawati, Wulan; Fareeha, Ardeli Zena El (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This paper aims to examine the legal construction of recognition for indigenous legal communities (MHA) in the Draft Law on Indigenous Peoples (RUU MHA) and analyze it within the context of Indonesia’s legal politics. Indigenous communities are a vital part of national diversity whose existence is acknowledged in Article 18B paragraph (2) of the 1945 Constitution. However, such recognition remains conditional and has yet to be effectively implemented. This research employs a normative legal method with statutory, historical, and conceptual approaches. The findings reveal that the RUU MHA offers a more comprehensive legal framework to secure the recognition of indigenous rights, including communal land, customary institutions, and freedom of belief. However, political challenges and overlapping regulations hinder its realization. In terms of legal politics, recognition of MHA is not yet a legislative priority, as seen in the delayed enactment of the bill since its inclusion in the 2012 National Legislation Program. Therefore, strong political will and legal reform are required to ensure that indigenous communities are fully recognized and protected. The RUU MHA is expected to become a legal instrument that fosters social justice and safeguards the rights of indigenous peoples in Indonesia.